Secondo Me - Cuzioc, Pavel
Secondo Me throws the spotlight on three cloakroom attendants at three European
opera houses: Vienna State Opera, La Scala in Milan, and Odessa Opera House. Sitting in the shadows of the operatic performances, the cloakroom attendants wait for the final act. Their work seems simple and monotonous. But their real lives, both inside and outside of the opera houses, are often more dramatic than events on stage
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films